2006
DOI: 10.1038/sj.cdd.4402056
|View full text |Cite
|
Sign up to set email alerts
|

Requirement for Daxx in mature T-cell proliferation and activation

Abstract: The protein Daxx promotes Fas-mediated cell death through activation of apoptosis signal-regulating kinase 1, leading to the activation of the MAPKs JNK and p38. Owing to the in utero lethality of daxx-deficient mice, the in vivo role of Daxx has been so far difficult to analyze. We have generated transgenic mice expressing a dominant-negative form of Daxx (Daxx-DN) in the T-cell lineage. We show that Daxx is recruited to the Fas receptor upon FasL engagement and that Daxx-DN expression protects activated T ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…It is a critical regulator of T-lymphocyte homeostasis by decreasing TCR-induced cell proliferation and by promoting Fas-mediated cell death [10]. Daxx has been shown that it acts as a scaffold that stimulates the phosphorylation of p53 by the protein kinase Hipk2 [11].…”
Section: Discussionmentioning
confidence: 99%
“…It is a critical regulator of T-lymphocyte homeostasis by decreasing TCR-induced cell proliferation and by promoting Fas-mediated cell death [10]. Daxx has been shown that it acts as a scaffold that stimulates the phosphorylation of p53 by the protein kinase Hipk2 [11].…”
Section: Discussionmentioning
confidence: 99%
“…33 As a novel histone chaperone and a product of an interferon-c-induced gene, Daxx has been extensively implicated in virus infection and T-cell activation. [34][35][36][37][38][39][40][41][42][43] Recent studies demonstrated that MST1 and Daxx interact with each other to mediate interferon-c-induced apoptosis in microglia, which plays a critical role during inflammation. 44 In this process, Daxx directly binds to MST1 and regulates its homooligomerization, activation and nuclear translocation.…”
Section: Gck-ii Kinases Regulate Lymphocyte Adhesion Migration Prolmentioning
confidence: 99%
“…Prior studies depended largely on the use of a dominant negative Daxx mutant, which may have unintended effects [2022]. For example, using the same Daxx-DN mutant, two independent studies reached opposing conclusions regarding the function of Daxx in Fas-induced apoptosis [27,28]. To date, the only other available system is a mouse Daxx -/- embryonic stem cell line, which was used in understanding a Fas-independent function for Daxx in controlling Mdm2 stability [37].…”
Section: Discussionmentioning
confidence: 99%
“…However, a subsequent study indicated that Daxx-DN inhibited Fas-induced apoptosis in primary T cells [28]. Therefore, whether Daxx plays a role in the Fas-signaling pathway has remained an unresolved issue.…”
Section: Introductionmentioning
confidence: 99%